2002
DOI: 10.1007/bf03402012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed Crystals of Hydroxyapatite and Brushite on the Crystallization of Calcium Oxalate in Undiluted Human Urine In Vitro: Implications for Urinary Stone Pathogenesis

Abstract: Background: The aim of this study was to determine whether crystals of hydroxyapatite (HA) or brushite (BR) formed in urine promote the epitaxial deposition of calcium oxalate (CaOx) from undiluted human urine in vitro and thereby explain the occurrence of phosphate in the core of urinary stones consisting predominantly of CaOx. Materials and Methods: Crystals of HA, BR, and CaOx were generated from human urine and their identity confirmed by X-ray analysis. Standard quantities of each crystal were then added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As a matter of fact, this was the only case in which Raman analysis was able to clearly detect the formation of Ca‐phosphates. Overall, we note that further considerations regarding different penetration depth and distribution of DAP and AmOx can be similarly made on the basis of the material porosity, on the formation mechanism of apatite and oxalate crystals as well as on their mutual interactions …”
Section: Discussionmentioning
confidence: 96%
“…As a matter of fact, this was the only case in which Raman analysis was able to clearly detect the formation of Ca‐phosphates. Overall, we note that further considerations regarding different penetration depth and distribution of DAP and AmOx can be similarly made on the basis of the material porosity, on the formation mechanism of apatite and oxalate crystals as well as on their mutual interactions …”
Section: Discussionmentioning
confidence: 96%
“…Several reports showing the presence of calcium carbonate (CaCO 3 ) in renal stones suggested that crystals of CaCO 3 might be present in the early steps of stone formation. Such crystals, therefore, might promote CaOx crystallization from supersaturated urine by providing an appropriate substrate for heterogeneous nucleation [143, 144]. …”
Section: Matrix Componentsmentioning
confidence: 99%
“…Once afflicted, the subsequent relapse rate is increased and the recurrence interval is shortened [2-5]. Moreover, its annual incidences are increasing and also the age of onset is decreasing, perhaps due to change in life styles, diet and climate [6]. …”
Section: Introductionmentioning
confidence: 99%